Role of the Constitutional Court in Indonesia's Electoral Justice System - Putra, Gede Dandi Pratama; Yusa, I Gede (IJBLE Scientific Publications Community Inc., 2026)
This study examines the position and authority of the Constitutional Court of Indonesia (Mahkamah Konstitusi) within the national electoral justice system and its institutional relationship with other electoral law enforcement bodies in realizing substantive electoral justice. Elections function as a core mechanism of constitutional democracy, requiring not only procedural legality but also effective judicial protection to ensure legitimacy and public trust. Using a normative legal research method, this study analyzes the 1945 Constitution of the Republic of Indonesia, the Election Law, the Constitutional Court Law, and other relevant statutory regulations through a statutory and conceptual approach. The findings show that the Constitutional Court holds strong constitutional legitimacy as the final and binding adjudicator of election result disputes. Its role has developed beyond merely correcting vote tabulations to assessing qualitative violations, particularly those that are structured, systematic, and massive, which affect the integrity of the electoral process. Furthermore, Indonesia's electoral justice system is implemented through an integrated framework involving the Election Supervisory Body (Bawaslu), the Honorary Council of Election Organizers (DKPP), the Integrated Law Enforcement Center (Sentra Gakkumdu), and the Constitutional Court. Each institution exercises distinct yet interrelated authority across administrative, ethical, criminal, and constitutional domains. This study concludes that the effectiveness of electoral justice in Indonesia depends not only on the Constitutional Court's final decisions but also on institutional synergy among electoral law enforcement bodies. Strengthening coordination and normative integration is essential to ensure that electoral justice is realized substantively, democratically, and constitutionally.